Changes in soil organic carbon under scenarios of land use change in Mexico - González Molina, Lucila; Acosta Mireles, Miguel; Carrillo Anzures, Fernando; Báez Pérez, Aurelio; González Camacho, Juan Manuel (Revista Mexicana de Ciencias Agrícolas, 2018)
Information regarding changes in soil organic carbon (SOC) due to change in land use of secondary vegetation tillage systems, scrub or grassland in Mexico is meager. This study was attended in 2011, at sites located in the States of Mexico, Hidalgo, Tlaxcala and Veracruz, in order to estimate changes in SOC under different scenarios of change in land use systems with secondary vegetation tillage systems, scrub or grassland, using the Rothamsted Carbon Model (RothC). The simulations were performed for a period of 40 years, taking into account: specific measurements of SOC in the study sites, the estimated C input into the soils of the plant residues and fertilizers, and the evaluation of RothC performance in sites and systems of Mexico. According to the results of simulation of scenarios of land use change, the use of conservation tillage systems under irrigated or rainfed conditions is the best alternative to conserve SOC stores and avoid loss of this element as CO2 emissions.
Keywords: agricultural systems; forestry systems; soil organic carbon (SOC); SOC dynamics